984 ADVANCE CARE PLANNING ON THE COMPLEX CARE WARDS AT ROYAL BOLTON HOSPITAL. (14th June 2022) - Green, S; Oates, R; Lim, V-H; Lennon, R; Woods, S
Abstract: Introduction: Advance care planning (ACP) is an important aspect of geriatric medicine, giving patients the opportunity to express their wishes and identify their preferred place of care and death whilst reducing unwanted hospital admissions. At Royal Bolton Hospital we reviewed the Complex Care department's performance in engaging with ACP discussions with appropriate patients and considered how this could be improved. Method: In October 2020, patients were identified from the current inpatients on the Complex Care wards using the following criteria: nursing home resident, clinical frailty score (CFS) 7 or above, or CFS 6 with 3 or more hospital admissions in the last 6 months. We reviewed the patient notes to ascertain whether any ACP had occurred and then followed the patients up at 6 and 12 months. At 6 and 12 months we identified the mortality and readmission rates to quantify whether the patients had been appropriate for ACP. Results: 35 patients identified as appropriate for ACP. ACP had been conducted in 10 patients. At 6 months, 13 patients had died and 17 had had hospital readmissions, totalling 196 readmission days. At 12 months, 8 patients had died, and 8 patients had been readmitted to hospital, totalling 85 readmission days. Combining the data for the 6- and 12-month results revealed 21 patients had died and 25 had been readmitted to hospital, totalling 281 readmission days. Only 4 of the 35 patients had neither died nor been readmitted to hospital. Conclusion: Appropriate patients were accurately identified for ACP as confirmed by their subsequent mortality and readmission rates. However, there is scope for improving the quantity of ACP discussions by the Complex Care department in these patients. Further education for the medical staff, a patient leaflet and poster aimed at the ward juniors will be introduced with the aim of doing this.